Prevalence of primary dysmenorrhea and factors associated with its intensity among undergraduate students: a cross-sectional study - Habibi, Nahal; Huang, Mary Soo Lee; Gan, Wan Ying; Rejali, Zulida; Safavi, Sayyed Morteza (WB Saunders, 2015)
Primary dysmenorrhea is a womanhood problem around the world and negatively affects quality of life. This study was designed to investigate the prevalence of primary dysmenorrhea and to determine the factors associated with its intensity. A cross-sectional study was carried out among 311 undergraduate female students aged 18 to 27 years in Isfahan University of Medical Sciences, Iran. Socio-demographic characteristics and menstrual factors were obtained through interviews with the help of a pretested questionnaire. The prevalence of primary dysmenorrhea was 89.1%. Residing at home, younger age, lower number of years of formal education for the mother, positive family history of dysmenorrhea, higher severity of bleeding, and shorter menstrual period intervals were significantly associated with the higher intensity of primary dysmenorrhea. Primary dysmenorrhea is a common health concern among young women. Being aware of the factors that are associated with its intensity makes it possible for health professionals to organize better focused programs to reduce the adverse effects of dysmenorrhea.